Π‐Extended Diaza[7]helicenes by Hybridization of Naphthalene Diimides and Hexa‐peri‐hexabenzocoronenes. Issue 7 (30th November 2020) - Dusold, Carolin; Sharapa, Dmitry I.; Hampel, Frank; Hirsch, Andreas
Abstract: The synthesis of an unprecedented, π‐extended hexabenzocorene (HBC)‐based diaza[7]helicene is presented. The target compound was synthesized by an ortho ‐fusion of two naphthalene diimide (NDI) units to a HBC‐skeleton. A combination of Diels–Alder and Scholl‐type oxidation reactions involving a symmetric di‐NDI‐tolane precursor were crucial for the very selective formation of the helical superstructure via a hexaphenyl‐benzene (HPB) derivative. The formation of the diaza[7]helicene moiety in the final Scholl oxidation is favoured, affording the symmetric π‐extended helicene as the major product as a pair of enantiomers. The separation of the enantiomers was successfully accomplished by HPLC involving a chiral stationary phase. The absolute configuration of the enantiomers was assigned by comparison of circular dichroism spectra with quantum mechanical calculations. Abstract : Super naphthalene, super helix : A diaza[7]helicene was formed as the only isomer via the fusion of two naphthalene diimides (NDIs) to a hexabenzocorene (HBC) core, generating a fully conjugated superstructure with a wide lateral π‐extension of the inner heterohelix. The helical twist brings along an attractive spatial arrangement and affects the chemical and photophysical features. Isolation of the corresponding enantiomers was accomplished by HPLC on a chiral stationary phase and the absolute configurations were determined by comparison of their circular dichroism spectra with quantum mechanical calculations.